Comorbidity Patterns Among Patients With Opioid Use Disorder and Problem Gambling: ADHD Status Predicts Class Membership. Issue 3 (3rd July 2019) - Silbernagl, Marisa; Yanagida, Takuya; Slamanig, Rudolf; Fischer, Gabriele; Brandt, Laura
Abstract: Objective: Psychiatric comorbidities are highly prevalent among individuals affected by substance use disorders and those with non-substance-related addictive disorders such as gambling disorder. More recently, the frequent co-occurrence of substance use disorders and attention-deficit hyperactivity disorder (ADHD) has received particular attention. The aim of our study was to identify patterns of psychiatric comorbidity and to examine associations between patient group and ADHD status with class membership.Methods: Participants were patients with opioid use disorder enrolled in opioid maintenance treatment (OMT), either recruited from the community ( n  = 142; M age = 35.8 years; 38.7% female) or prison ( n  = 133; M age = 35.7 years; 21.8% female), and patients undergoing treatment for problem gambling (PrG; n  = 80; M age = 43.1 years; 20% female). To enable direct comparisons, the following instruments were applied: Mini International Neuropsychiatric Interview, Adult ADHD self-report scale, Wender Utah Rating Scale, and European Addiction Severity Index. We used a latent class analysis (LCA) to identify psychiatric comorbidity patterns and a multinomial logistic regression to examine associations between patient group, ADHD status, age, and gender with class membership.Results: The LCA resulted in a three-class solution: (1) a class of individuals with a relatively low probability of current psychiatric comorbidities, except for a high probability of substance use disorders; (2) a class with markedly increased probabilities of current and recurrent psychiatric comorbidities, especially for major depression; and (3) a class with very low probabilities of psychiatric comorbidities, except for moderate probabilities of substance use disorders and antisocial personality disorder. Both OMT patients recruited from the community and those in prison were less likely than PrG patients to be assigned to the most burdened class with respect to psychiatric comorbidity (class 2). Further, both individuals with ADHD in childhood and those with adult ADHD were more likely members of class 2.Conclusions: PrG patients seem to be at an even higher risk for psychiatric comorbidities compared to OMT patients. Raising awareness among practitioners for the high prevalence of psychiatric comorbidities among patients with gambling disorder and individuals with ADHD is crucial to initiate adequate treatment and to improve response.